Exit from Brain Device Research: A Modified Grounded Theory Study of Researcher Obligations and Participant Experiences. Issue 4 (2nd October 2022) - Sankary, Lauren R.; Zelinsky, Megan; Machado, Andre; Rush, Taylor; White, Alexandra; Ford, Paul J.
Abstract: As clinical trials end, little is understood about how participants exiting from clinical trials approach decisions related to the removal or post-trial use of investigational brain implants, such as deep brain stimulation (DBS) devices. This empirical bioethics study examines how research participants experience the process of exit from research at the end of clinical trials of implanted neural devices. Using a modified grounded theory study design, we conducted semi-structured, in-depth interviews with 16 former research participants from clinical trials of DBS and responsive neurostimulation (RNS). Open-ended questions elicited motivations for joining the trial, understanding of study procedures at the time of initial informed consent, the process of exiting from research, and decisions about device removal or post-trial device use. Thematic analysis identified categories related to: limited preparedness for the end of research participation, straightforwardness of decisions to explant or keep the device, reconciling with the end of research participation, reconciling post-trial expectations, and achieving a sense of closure after exit from research. A preliminary theoretical model describes contextual factors influencing the process and experience of exit from research. Experiences of clinical trial participants should guide research practices to enhance the ethical design and conduct of clinical trials in DBS and other brain devices.